FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN RESTAURANT ALPHA HOTEL PEKANBARU - Wahyuni "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Alpha Hotel under the management of PT. One Six Eight Together that is scattered in a very strategic area in Pekanbaru, namely on Jalan Haji Imam Munandar No. 17, which is about 10 to 15 minutes from the Sultan Syarif Kasim II International Airport, Pekanbaru. Alpha Hotel was established on February 27, 2012 and is recorded in AKTA number 45, validated at the SUTRISNO ARSJAD, SH notary office. This hotel is a branch of Alpha Inn Hotel located in Medan, North Sumatra. Alpha Hotel Pekanbaru began operating as of December 14, 2013. The Importance of an Alpha Hotel Pekanbaru's employee performance factors is very influential on the performance of restaurant employees. Performance is the result of the quality achieved by an employee in performing according to their duties and responsibilities given to him. This study uses qualitative methods, the factors discussed in this case are Employee Performance Measures and Factors that affect performance. While the data collection techniques used in this study, in-depth interviews and documentation. The key informants in this study were 4 restaurant employees. Based on the results of research conducted, for the overall results of the interview said that the performance of Restaurant employees is still improving. Keywords: Employee, Performance and Factors .